REVIEW ON THE RECENT SAMPLE PREPARATION METHODS FOR THE ANALYSIS OF TOXIC HEAVY METALS IN FOODS AND BEVERAGES - Akilu, Aminu; Abubakar Lawal (FUDMA JOURNAL OF SCIENCES, 2025)
This review critically assesses conventional and emerging sample preparation techniques for analyzing toxic heavy metals in foods and beverages. It highlights limitations of traditional methods like wet and dry ashing such as time consumption, potential analyte loss, and high solvent use while introducing efficient alternatives QuEChERS and DLLME. Analysis of studies, particularly on Nigerian food staples, reveals that wet ashing offers superior metal recovery over dry ashing. Alarmingly, lead and cadmium levels often exceed WHO/FAO safety limits, indicating serious health risks. The emerging methods are presented as cost-effective, efficient, and greener alternatives that overcome the drawbacks of conventional approaches. The findings emphasize the urgent need for robust monitoring programs and the adoption of advanced techniques to ensure food safety and protect public health. Future research should focus on validating these methods across diverse food matrices.